Effect of bariatric surgery on semen parameters and sex hormone concentrations: a prospective study. Issue 5 (November 2016) - El Bardisi, Haitham; Majzoub, Ahmad; Arafa, Mohamed; AlMalki, Ahmad; Al Said, Sami; Khalafalla, Kareim; Jabbour, Gaby; Basha, Moataz; Al Ansari, Abdulla; Sabanegh, Edmund
Abstract: Obesity has become a major health concern, with a prevalence rate approaching epidemic states. An inverse relationship between men′s body weight and semen parameters has been observed, suggesting a favourable role for weight loss in improving fertility. This prospective study included 46 patients undergoing sleeve gastrectomy, who were investigated with semen analysis and serum hormone tests before and 12 months after surgery. Patients were divided into three groups according to their initial sperm concentration; median loss of body mass index was used as a cut-off to further classify patients according to extent of weight loss. Patients' preoperative seminal investigations revealed azoospermia in 13 (28.3%), oligospermia in 19 (41.3%) and normal sperm concentration in 14 (30.4%). Overall, only serum testosterone significantly increased after surgery ( P < 0.001). Between study groups, the increase in sperm concentration was statistically significant in men with azoospermia and oligospermia (both P < 0.05), whereas serum testosterone was statistically significant in all groups ( P < 0.001). Changes in semen and hormone tests were not affected by the extent of weight loss experienced by patients. Weight loss from bariatric surgery had a favourable effect on serum testosterone levels and semen parameters of patients with pre-existing azoospermia and oligospermia.